Corporate social responsibility, origin and relevance - Encinas Palafox, Wendy Carolina (Posgrados de la División de Ciencias Económica Administrativas, 2021)
The economic and social progress brought with it important consequences derived from irresponsible actions in the use and consumption of the planet's resources, which compromises the future of the next generations. In this context, the business sector, in its concern the counter made by the damage, implemented socially responsible actions that in turn are profitable for the company, naming this corporate social responsibility. On the other hand, the interest of consumers in these practices is growing and they are beginning to get involved through more conscious consumption. The purpose of this article is to show a literature review about the evolution of Corporate Social Responsibility, its relationship with marketing, and its relevance in the current environment. To achieve this objective was applied a methodology of articles exploration in major magazines carried out based on the origin of the concept, evolution and its implications for business and society. It is observed that there are numerous studies throughout history that have led to consolidating the term Corporate Social Responsibility, however, although companies currently recognize the concept, they still lack implementation in their business, and marketing strategies.